Pattern recognition receptor immunomodulation of innate immunity as a strategy to limit the impact of influenza virus. Issue 4 (3rd November 2016) - Pizzolla, Angela; Smith, Jeffery M; Brooks, Andrew G; Reading, Patrick C
Abstract : Review on strategies targeting cell-associated PRRs to elicit protective innate responses, and/or to augment vaccine efficacy against influenza. Abstract: Influenza remains a major global health issue and the effectiveness of current vaccines and antiviral drugs is limited by the continual evolution of influenza viruses. Therefore, identifying novel prophylactic or therapeutic treatments that induce appropriate innate immune responses to protect against influenza infection would represent an important advance in efforts to limit the impact of influenza. Cellular pattern recognition receptors (PRRs) recognize conserved structures expressed by pathogens to trigger intracellular signaling cascades, promoting expression of proinflammatory molecules and innate immunity. Therefore, a number of approaches have been developed to target specific PRRs in an effort to stimulate innate immunity and reduce disease in a variety of settings, including during influenza infections. Herein, we discuss progress in immunomodulation strategies designed to target cell-associated PRRs of the innate immune system, thereby, modifying innate responses to IAV infection and/or augmenting immune responses to influenza vaccines.